CFD modelling and performance increase of a pusher type reheating furnace using oxy-fuel burners. (August 2017) - Mayr, Bernhard; Prieler, Rene; Demuth, Martin; Moderer, Luca; Hochenauer, Christoph
Abstract: In conventional combustion systems which use air as oxidizer, a huge amount of the heat of formation is absorbed by the nitrogen in the air. In oxygen enriched or oxy-fuel combustion an O2 /N2 -mixture with a higher concentration of oxygen is used. Due to the lower amount of nitrogen in the oxidizer the flame temperature increases and radiative heat transfer is improved in the furnace. Therefore, the influence of additional oxy-fuel jet burners on the productivity of a pusher type reheating furnace is investigated in this paper. Due to the special arrangement of the billet in this type of furnace the billets can be treated as a fluid with a very high viscosity. Therefore, the periodic transient reheating of the billets and the gas phase combustion was calculated in one steady state calculation. The combustion in the gas phase is described by the steady laminar flamelet approach for air-fuel combustion and the eddy dissipation concept model is used in the simulation with the oxy-fuel burners. The results of the gas phase simulation with air as oxidizer was validated with measurements and showed an average deviation of 38 K. The calculated billet temperature was also compared to the measurements and showed deviation of 27 K which can be seen as a good agreement. With this model the influence of additional oxy-fuel burners is investigated. The investigation showed that with additional oxy-fuel burners the productivity of the furnace can be increased from 60 t/h to 68 t/h and furthermore the furnace efficiency increases from 62.9% to 65%. This shows the beneficial effect of using oxy-fuel combustion.